2009
DOI: 10.1111/j.1582-4934.2009.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial glycocalyx dimensions are reduced in growing collateral arteries and modulate leucocyte adhesion in arteriogenesis

Abstract: During collateral artery growth, monocytes adhere to the endothelium and secrete cytokines from the perivascular space promoting arteriogenesis. Recently, the endothelial glycocalyx has been shown to modulate leucocyte infiltration in atherogenic regions. The role of this endothelial surface coating in arteriogenesis, however, has not been investigated so far. We now report that local plasma levels of hyaluronic acid are specifically increased in collateral arterial blood of coronary artery disease patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…The assumption of steric hindrance of interactions between leukocyte and EC through the glycocalyx is supported by the fact that adhesion of leukocytes to the endothelium increases on the enzymatic removal of the glycocalyx. 34,35 This finding was complemented in the present study by increased macrophage retention in vascular lesions after short-term and long-term treatment with 4-MU. Furthermore, 2-week treatment with 4-MU also increased the number of macrophages that were recruited in an acute model of inflammation.…”
Section: Nagy Et Al Hyaluronan Synthesis and Atherosclerosis 2319supporting
confidence: 71%
“…The assumption of steric hindrance of interactions between leukocyte and EC through the glycocalyx is supported by the fact that adhesion of leukocytes to the endothelium increases on the enzymatic removal of the glycocalyx. 34,35 This finding was complemented in the present study by increased macrophage retention in vascular lesions after short-term and long-term treatment with 4-MU. Furthermore, 2-week treatment with 4-MU also increased the number of macrophages that were recruited in an acute model of inflammation.…”
Section: Nagy Et Al Hyaluronan Synthesis and Atherosclerosis 2319supporting
confidence: 71%
“…Grundmann et al [20] recently reported that local plasma levels of hyaluronic acid are specifically increased in collateral arterial blood. In addition, tissues enriched in HA may undergo expansion because of the ability of the molecule to bind to large amounts of water, thus creating a loose, hydrated microenvironment that facilitates cell migration and proliferation, which are two critical events in angiogenesis and arteriogenesis [21].…”
Section: Discussionmentioning
confidence: 98%
“…Unilateral femoral artery occlusion was performed in C57/Bl6J mice (Charles River Lab., Sulzfeld, Germany) under anaesthesia with ketamin and xylazin by double ligation of the superficial femoral artery proximal to the deep femoral artery and the distal femoral artery just above the knee joint as previously described [17], [18]. Tissue of the gastrocnemius and soleus muscles was carefully dissected from the lower leg and snap-frozen in liquid nitrogen until further analysis.…”
Section: Methodsmentioning
confidence: 99%